TEMPORAL VARIATION AND SPATIAL DISTRIBUTION OF RELATIVE INDICES OF LEAF CHLOROPHYLL IN GRAPEVINE cv. CHARDONNAY - Costa, Bruno R. S. [UNESP]; Oldoni, Henrique [UNESP]; Silva, Wendell A. [UNESP]; Martins, Roberto L. [UNESP]; Bassoi, Luis H. (Soc Brasil Engenharia Agricola, 2019)
Variation in the spatial distribution of leaf chlorophyll content associated with the progression of the phenological cycle of crops may occur in cultivated areas as a result of the variability of environmental conditions and of the intrinsic properties of the plants. The objective of the present study was to model the trend in variation and assess the temporal stability of index of chlorophyll a, b, and total chlorophyll (Chl(a), Chl(b), and Chl(t), respectively), and to characterize the spatial distribution of Chl(t) index in grapevine cv. 'Chardonnay'. The assessments consisted of in situ measurements made with a portable meter in a commercial vineyard located in the municipality of Espirito Santo do Pinhal, state of Sao Paulo, Brazil, in the period between flowering and fruit maturation. Descriptive statistics were applied to the indices and regression models were fitted to ascertain the relationship of their mean variation with time. The temporal stability of Chl(t) index was estimated using Spearman's rank correlation analysis and thematic maps were created using geostatistical analysis and spatial estimation by ordinary kriging. The Chl(b) and Chl(t) indices were non-linearly associated with cycle progression and their decrease after the start of maturation was estimated. The temporal stability of the Chl(t) index was low and variation in its spatial distribution was observed over the assessed period.
Keywords: Vitis vinifera L.; photosynthetic pigments; portable meter